The Influence of English Language Proficiency on Professional Performance in the Sharia Economic Sector - Muhammad alhadifauzan; Kuran Nila; M.Adrius Arjuanda (Penerbit Hellow Pustaka, 2025)
English language proficiency is a strategic competency in facing economic globalization, particularly in the sharia economic sector, which has shown significant growth and increasing involvement in international financial networks. This study aims to analyze the influence of English language skills on the professional performance of workers in the sharia economic sector, focusing on the relationship between linguistic abilities and performance indicators such as work efficiency, cross-cultural communication, and the accuracy of professional reports. The study employs a qualitative approach using the library research method, reviewing relevant national and international scientific literature from 2020 to 2024. Data were collected through systematic documentation and analyzed thematically using a descriptive-analytical approach. The findings reveal that English language proficiency, particularly in the context of English for Specific Purposes (ESP), significantly contributes to the improvement of professional work quality in Islamic financial institutions, halal companies, and other supporting institutions. The study also identifies limitations in learning motivation, availability of ESP instructors, and contextual teaching materials as major obstacles in strengthening language competencies. The conclusion affirms that mastery of the English language not only supports individual performance but also serves as a key factor in enhancing the global competitiveness of sharia human resources. This study offers a conceptual contribution to the theory of multilingual professional competence and provides a practical foundation for formulating language training policies in the sharia economic sector.